The Effectiveness of Family Centered Maternity Care (FCMC) Education to Increase The Independence of Pospartum Mother - Senditya Indah Mayasari; Byba Melda Suhita; Indasah Indasah (Health Notions, 2018)
Family Cenetered Maternity Care (FCMC) Education is family-centered care by providing care for women and their families that integrate pregnancy, delivery, childbirth, and infant care into the continuum of the family life cycle as usual through healthy living. The care given to the individual prioritizes the support, participation, and choice of the family. Treatments that need to be done in the puerperium are breast care for breastfeeding and postpartum perineal care to avoid infection. The study was conducted with the aim to know the Effectiveness of Family Centered Maternity Care (FCMC) Education in Increasing Independence of Postpartum Mother in Malang Regency. The research type is true experimental with Pretest-Posttest Design approach. Sampling is done by systematic random sample. Data collection was obtained with questionnaires to postpartum physiologic mothers as many as 12 postpartum mothers in the intervention and control group. Result showed after being educated almost all (92%) of respondents have been self-sufficient in breast care, independence in perineal care at 83% independent level and 8% light dependence. FCMC education can increase independence in care needs during the puerperium. Breast care is done to prepare the lactation process, especially during the puerperium for the baby's nutritional needs. While perineum treatment is done to maintain hygiene and prevent infection in the vulva, perineum in the uterus and perineum wound healing. Keywords: Postpartum, FCMC, Self-reliance, Breast care, Perineal care